Cómo afectan distintos cultivos de cobertura las emisión de óxido nitroso del cultivo siguiente? - Vangeli, Sebastián; Restovich, Silvina Beatriz; Azich, Pablo; Adrover, Carol; Villalba, Fabio Leonardo; Colombini, Diego Alberto; Posse Beaulieu, Gabriela (Asociación Argentina de la Ciencia del Suelo, 2021)
Poster